Imaging Tissue Physiology In Vivo by Use of Metal Ion-Responsive MRI Contrast Agents - Pooyan Khalighinejad; Daniel Parrott; A. Dean Sherry (MDPI AG, 2020)
Paramagnetic metal ion complexes, mostly based on gadolinium (Gd3+), have been used for over 30 years as magnetic resonance imaging (MRI) contrast agents. Gd3+-based contrast agents have a strong influence on T1 relaxation times and are consequently the most commonly used agents in both the clinical and research environments. Zinc is an essential element involved with over 3000 different cellular proteins, and disturbances in tissue levels of zinc have been linked to a wide range of pathologies, including Alzheimer's disease, prostate cancer, and diabetes mellitus. MR contrast agents that respond to the presence of Zn2+ in vivo offer the possibility of imaging changes in Zn2+ levels in real-time with the superior spatial resolution offered by MRI. Such responsive agents, often referred to as smart agents, are typically composed of a paramagnetic metal ion with a ligand encapsulating it and one or more chelating units that selectively bind with the analyte of interest. Translation of these agents into clinical radiology is the next goal. In this review, we discuss Gd3+-based MR contrast agents that respond to a change in local Zn2+ concentration.